Pengaruh Budaya Organisasi Dan Lingkungan Kerja Dengan Motivasi Sebagai Variabel Intervening Terhadap Kinerja Karyawan (Studi pada Teller Bank Kalsel Cabang Utama Banjarmasin) - Isliana, Noor; Ghalib, Saladin (Universitas Lambung Mangkurat, 2023)
This study aims to examine the effect of Organizational Culture and Work Environment with Motivation as an Intervening Variable on Teller Employee Performance at Bank Kalsel Main Branch Banjarmasin. The approach used in this research is quantitative, with the type of causality associative research. The sampling method used nonprobability sampling with saturated sampling method on 32 employees of Teller Bank Kalsel Main Branch Banjarmasin. The google form questionnaire was distributed via Whatsapp to each respondent. Data analysis using SmartPLS softwareThe results showed that Organizational Culture had an insignificant effect on the Performance of Teller Employees of Bank Kalsel Main Branch Banjarmasin, Work Environment had a significant effect on Employee Performance of Teller Employees of Bank Kalsel Main Branch of Banjarmasin, Organizational Culture had a significant influence on Motivation of Teller Employees of Bank Kalsel Main Branch Banjarmasin, The work environment has a significant influence on the motivation of teller employees at Bank Kalsel Main Branch Banjarmasin and motivation has an insignificant effect on the performance of teller employees at Bank Kalsel Main Branch Banjarmasin. While indirectly Organizational Culture has an insignificant effect on Employee Performance mediated by motivation at Bank Kalsel Main Branch Banjarmasin and Work Environment has an insignificant effect on Employee Performance mediated by motivation at Bank Kalsel Main Branch Banjarmasin Keywords: Organizational Culture, Work Environment, Motivation, Employee Performance